2013
DOI: 10.1159/000354380
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Keratitis

Abstract: Neurotrophic keratitis (NK) is a rare degenerative corneal disease that occurs as a result of partial or total impairment of trigeminal innervations, leading to a reduction (hypoesthesia) in or loss (anaesthesia) of corneal sensitivity. The impairment of sensory innervation causes a reduction in the lacrimation reflex and the vitality, metabolism and mitosis of epithelial cells, with subsequent deficiency in epithelial repair, stromal and intracellular oedema, loss of microvilli, and abnormal development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(130 citation statements)
references
References 51 publications
1
127
0
2
Order By: Relevance
“…It is likely that initiation of consensual BR in the contralateral eyes of these patients is impaired, which could cause corneal desiccation that amplifies the severity and chronicity of virus-induced immunopathology in the infected eye. Indeed, dry eye and neurotrophic damage to the cornea can be associated with HSK in humans (34,35). Our studies demonstrate for the first time that corneal desiccation associated with total loss of corneal BR is a major contributing factor in the severe and chronic inflammation that develops in mice with HSK.…”
Section: Discussionmentioning
confidence: 65%
“…It is likely that initiation of consensual BR in the contralateral eyes of these patients is impaired, which could cause corneal desiccation that amplifies the severity and chronicity of virus-induced immunopathology in the infected eye. Indeed, dry eye and neurotrophic damage to the cornea can be associated with HSK in humans (34,35). Our studies demonstrate for the first time that corneal desiccation associated with total loss of corneal BR is a major contributing factor in the severe and chronic inflammation that develops in mice with HSK.…”
Section: Discussionmentioning
confidence: 65%
“…In humans, it was observed that the impairment of corneal innervation can cause corneal ulcers (neurotrophic keratitis) [49]. Patients with neurotrophic keratitis present decreased corneal sensitivity with alterations in corneal epithelium, nerve, keratocyte, and endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic keratitis is a potentially blinding condition whose corneal pathology (cloudiness, erosions, dry surface, increased risk of infections) results from reduced innervation of the cornea by stromal and ICNs (Sacchetti and Lambiase, ; Semeraro et al, ; Shaheen et al, ). It occurs secondary to neuropathy of the trigeminal nerve or after ocular surgery, trauma, and/or viral infections.…”
Section: Sbn Loss Stops Corneal Epithelial Cell Proliferationmentioning
confidence: 99%